Unlocking the complete chloroplast genome of a native tree species from the Amazon Basin, capirona (Calycophyllum spruceanum, Rubiaceae), and Its comparative analysis with other Ixoroideae species - Saldaña Serrano, Carla Lizet; Rodriguez Grados, Pedro Manuel; Chávez Galarza, Julio César; Feijoo Narvasta, Shefferson Gilbert Wilson; Guerrero Abad, Juan Carlos; Vásquez Pérez, Héctor Vladimir; Maicelo Quintana, Jorge Luis; Jhoncon, Jorge H.; Arbizu Berrocal, Carlos Irvin (MDPI, 2023)
Capirona (Calycophyllum spruceanum Benth.) belongs to subfamily Ixoroideae, one of the major lineages in the Rubiaceae family, and is an important timber tree. It originated in the Amazon Basin and has widespread distribution in Bolivia, Peru, Colombia, and Brazil. In this study, we obtained the first complete chloroplast (cp) genome of capirona from the department of Madre de Dios located in the Peruvian Amazon. High-quality genomic DNA was used to construct libraries. Pair-end clean reads were obtained by PE 150 library and the Illumina HiSeq 2500 platform. The complete cp genome of C. spruceanum has a 154,480 bp in length with typical quadripartite structure, containing a large single copy (LSC) region (84,813 bp) and a small single-copy (SSC) region (18,101 bp), separated by two inverted repeat (IR) regions (25,783 bp). The annotation of C. spruceanum cp genome predicted 87 protein-coding genes (CDS), 8 ribosomal RNA (rRNA) genes, 37 transfer RNA (tRNA) genes, and one pseudogene. A total of 41 simple sequence repeats (SSR) of this cp genome were divided into mononucleotides (29), dinucleotides (5), trinucleotides (3), and tetranucleotides (4). Most of these repeats were distributed in the noncoding regions. Whole chloroplast genome comparison with the other six Ixoroideae species revealed that the small single copy and large single copy regions showed more divergence than inverted regions. Finally, phylogenetic analyses resolved that C. spruceanum is a sister species to Emmenopterys henryi and confirms its position within the subfamily Ixoroideae. This study reports for the first time the genome organization, gene content, and structural features of the chloroplast genome of C. spruceanum, providing valuable information for genetic and evolutionary studies in the genus Calycophyllum and beyond.